Lucian Verae historiae 2.20 and the Relative Chronology of the Homeric Poems. - Lionetti, Ruggiero (Classical Philology, 2023)
At Lucian Verae historiae 2.20 Homer is asked "whether he wrote the Odyssey before the Iliad , as most people say." In the form in which it is transmitted, the text implies that the view that the Odyssey was composed before the Iliad was the (by far) prevailing one in antiquity. This paper argues that such an assumption is contradicted by all the positive evidence provided by literary sources and scholiography. The problem can be solved by correcting the transmitted τὴν Ὀδύσσειαν τῆς Ἰλιάδος into τῆς Ὀδυσσείας τὴν Ἰλιάδα. Thus emended, the passage reads: "whether he wrote the Iliad before the Odyssey , as most people say."